The Matic Exploratory of Content Marketing for the Fourth Industrial Revolution - Ajayi Olalekan Ezekiel (PT FORMOSA CENDEKIA GLOBAL, 2022)
The marketing world is a dynamic and constantly changing environment that never stagnates. The fourth industrial revolution refers to a set of new technologies that are integrating the physical, digital, and biological worlds, affecting all disciplines, economies, and sectors, and even questioning what it is to be human. The purpose of this paper is to investigate and analyzed, how important is a content marketing strategy to the customers in the era of the fourth industrial revolution. The presented paper consists of three parts, the first part of the paper focuses on theoretical aspects of content marketing. The second part focuses on methods of data collection that are needed to perform analysis. This research work makes use of secondary data. Relevant data for this study was collected from already published/online materials, articles, Newspapers, journals, archives, web postings as well as editorials. The method of analysis that was employed in this study is systematic qualitative content analysis. The result of this paper is a comprehensive overview of thematic exploratory content marketing strategy that can be used to influence user interests in the global market and how important is communication with customers.